Population Age Structure Change and Labour Productivity: Evidence from Tunisia - Frini, Olfa; Jedidia, Khoutem Ben (The European Journal of Applied Economics, 2019)
Relying on a macroeconomic view, this paper investigated the popula-tion ageing effect on the aggregate labour productivity. It examined the effects of the labour force participation rate through three broad age ranges: young adulthood (15-29), prime age (30-49) and old age (50-64). It computed the labour force participation rate by age considering the working-age of the same age range. Using Tunisian data covering the years 1965-2014, the cointegration method testified for a long-run relationship with a progressive adjustment process towards equilibrium. Unlike the conventional approach outcome, the age-productivity profile in our study did not follow an inverted U-shape. Labour productiv-ity edged down for young workers, rose for the prime age adults, and kept on rising for older people. Accordingly, population ageing did not alter the Tunisian labour market performance. Thus, to achieve better productivity gains and enhance the country’s economic growth, delaying the retirement age beyond 60 was advocated.